2017
DOI: 10.1016/j.ophtha.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Leber Hereditary Optic Neuropathy

Abstract: OBJECTIVE To determine the effects of escalating doses of AAV2(Y444,500,703F)-P1ND4v2 in patients with LHON caused by the G11778A mutation in mitochondrial DNA. DESIGN Prospective open-label, unilateral single-dose, intravitreal injection of AAV2(Y444,500,703F)-P1ND4v2 per subject in a phase I clinical trial study initiated in 2014. PARTICIPANTS Fourteen patients with visual loss and mutated G11778A mitochondrial DNA. INTERVENTION Intravitreal injection with the gene therapy vector AAV2(Y444,500,703F)-P1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
1
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(166 citation statements)
references
References 22 publications
6
140
1
19
Order By: Relevance
“…[25][26][27] This occurrence would ultimately cause localized tissue inflammation and reduced therapeutic efficacy, and it may underlie the cases of intraocular inflammation encountered in retinal gene therapy trials. [14][15][16] The upregulation of innate immune mediators detected on day 7 post-subretinal gene therapy in vivo does not rule out the presence of background levels of pre-existing surveillance innate sensors. Active AAV particles may be present within the subretinal space for a prolonged period (e.g., days) during which repeated waves of viral entry into the host cells may occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] This occurrence would ultimately cause localized tissue inflammation and reduced therapeutic efficacy, and it may underlie the cases of intraocular inflammation encountered in retinal gene therapy trials. [14][15][16] The upregulation of innate immune mediators detected on day 7 post-subretinal gene therapy in vivo does not rule out the presence of background levels of pre-existing surveillance innate sensors. Active AAV particles may be present within the subretinal space for a prolonged period (e.g., days) during which repeated waves of viral entry into the host cells may occur.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Consequently, despite promising results seen with retinal gene therapy, cases of intraocular inflammation have been encountered. [14][15][16] Therefore, one of the major challenges of gene therapy for retinal diseases is how to achieve sufficient levels of gene replacement at a safe vector dose.…”
Section: Introductionmentioning
confidence: 99%
“…Additional results for this study have been recently published and showed an improvement in average acuity for 12 subjects with LHON and bilateral visual loss who received unilateral treatment. This study also demonstrated the safety of allotropic gene therapy for LHON [92]. …”
Section: Gene Therapymentioning
confidence: 80%
“…There are several AAV‐based clinical trials registered for LHON disease and one has been completed using allotopic expression of ND4, that is expression of mtDNA‐encoded protein from the nucleus. Although there is weak evidence that allotopically expressed mtDNA‐encoded subunits can enter into mitochondria and can be inserted into respiratory complexes, Guy et al reported amelioration of visual acuity in the injected eyes [119]. An alternative explanation to this clinical effect could be the presence of a secondary mutation in mtDNA and a spontaneous recovery that is often observed especially in the m.11778G> A mutation [120].…”
Section: Supplementation Of Coqmentioning
confidence: 99%